Development and validation study of the suicide screening questionnaire-observer rating (SSQ-OR) - Choi, Young-Hwan; Yook, Vidal; Yang, Kyojin; Cho, Yaehee; Lee, Deok Hee; Lee, Hwa Jung; Lee, Dong Hun; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
Background: Observer rating scales are necessary to evaluate the risk of suicide because individuals at risk for suicide are often unwilling to seek help on their own. Reliability and validity were evaluated for the newly developed Suicide Screening Questionnaire-Observer Rating (SSQ-OR). Methods: Preliminary items were assessed by 251 experts online and 25 questions were selected. 328 individuals at high-risk and 661 controls from 12 Crisis Response Centers and 5 university counseling centers were recruited to complete SSQ-OR, Beck Scale for Suicide Ideation (BSSI) and Patient Health Questionnaire-9 (PHQ-9). In a six months follow-up, we reached out to 176 participants to ask whether they had experienced a suicidal thought, plan, or attempt since the baseline assessment. Cronbach's α, Mann-Whitney U test, Spearman's correlation, factor analyses, Receiver operating characteristic (ROC) analysis and logistic regression analysis were used to verify the SSQ-OR. Results: Structural validity was supported by a two-factor solution using exploratory and confirmatory factor analyses. Excellent model fit indices for the two-factor structure using exploratory factor analysis were confirmed (RMSEA=0.033, TLI=0.980, CFI=0.983). The SSQ-OR demonstrated strong internal consistency. The concurrent validity based on the correlations with other self-reported indicators of suicidal potential–BSSI and PHQ-9– revealed substantial relationships. The high-risk group was effectively characterized by a cut-off point of 4, with a sensitivity of 0.73 and a specificity of 0.79. The SSQ-OR scores were significant predictors of suicidal thoughts and behaviors within six months. Conclusions:. The SSQ-OR exhibits sound psychometric properties, and could be used as a complement to a self-report or clinical-administered scale to screen suicide risk comprehensively.